Synthesis, Characterization and Biological Evaluation of Some 2-Azetidinones Derivative from Benzimidazole and Used as Anti-Fungicide Agents - Ahmood Kh. Jebur Al-Joubory (Journal of Global Pharma Technology, 2016)
Reaction of benzimidazole with ethyl chloro acetate to give ethyl –N–benzimidazole acetate (M1) which was used the reaction with hydrazine hydrate to yield N- benzimid azole aceto hydrazide (M2). The reaction of compound (M2) with different aromatic aldehydes gave compounds hydrazone (M3, M4). (P-Hydroxy (or Chloro) benzylidine) -N- aceto hydrazide benzimidazole. Then the compounds (M3, M4) reacted with chloro acetyl chloride in presence of tri ethyl amine using DMF as solvent to obtain 2-azetidinones compounds (M5, M6). The structures of all the newly synthesized compounds were confirmed by elemental analysis and FT-IR, 1H NMR and 13C NMR as well as melting point. Some of these compounds showed good antimicrobial activity (M1-M6) and anti-bacterial activity (M1-M6) Antibacterial activity of some prepared compounds against two types of bacteria: Staphylococcus aureus (Gram positive) and E.coli (Gram negative). Some the compounds showed high inhibition activity against bacteria and two fungi (Candida albicans).Keywords: Benzimidazole, Schiff bases, Ester, Heterocyclic compounds.